Abnormalities of Quantitative Electroencephalography in Children with Asperger Disorder Using Spectrogram andCoherence Values - Hamid Behnam; Ali Sheikhani; Maryam Noroozian; Mohammad Reza Mohammadi (Iranian Journal of Psychiatry, 2008)
"n  "n  "nObjective:To obtain abnormalities in quantitative Electroencephalography QEEG) and to observe connectivity between electrodes in children with Asperger disorder. "n  "n  "nMethod: "nIn this study, spectrogram criteria and coherence values are used as a tool for evaluating QEEG in 15 children with Asperger disorder (10 boys and 5 girls aged between 6 to 11 years old) and in 11 control children boys and 4 girls with the same age range). "n  "n  "nResults: "nThe evaluation of QEEG using statistical analysis and spectrogram criteria demonstrates that the relaxed eye-opened condition in gamma frequency band (34-44Hz) has the best distinction level of 96.2% using spectrogram. The children with Asperger disorder had significant lower spectrogram criteria values (p<0.01) at Fp1 electrode and lower values (p<0.05) at Fp2 and T6 electrodes. Coherence values at 171 pairs EEG electrodes indicate that the connectivity at (T4, P4), (T4, Cz), (T4, C4) electrode pairs and (T4, O1) had significant differences (p<0.01) in the two groups in the gamma band. "n  "n  "nConclusions: "nIt is shown that gamma frequency band can discriminate 96.2% of the two groups using the spectrogram criteria. The results demonstrate that there are more abnormalities in the prefrontal and right temporal lobes using spectrogram criteria and there are more abnormalities "nthe connectivity of right temporal lobe with the other lobes in the gamma "nfrequency band.